Teacher Response on Using Classkick Application as a Mandarin Learning Media - Yetty Go; Ruomei Fu; Mariana Mariana (Jurnal Sinestesia, 2022)
Nowadays, there are so many inventions and development of interactive web-based applications or mobile app tools as a promising tool for creating more active online learning. The use of learning media as a learning tool is an effort made by teachers to make learning more fun, effective, and interesting. One of the examples is the Classkick application learning media. Using Classkick application as a learning media in Mandarin classes could help teachers to achieve learning goals. With the interesting and varied features of the Classkick application such as audio, video, and text, it can help teachers design more varied exercises to practice students' four mandarin language skills (listening, speaking, reading, and writing). The study aims to identify teachers' responses to the use of Classkick application as a learning media in Mandarin classes. The methodology approach of this study is qualitative research and adapted Yanqun’s five characteristics of learning media as a theory. The study determines that the features of Classkick application can help teachers design varied exercises and assignments that can increase students' enthusiasm for learning and practice students' Mandarin language ability. It also can bridge the communication gap between teacher and students, teachers are also able to monitor and provide feedback on students’ works in real-time during the online or offline classes.